Spectrophtometric determination of Hydrochlorothiazaide by oxidative coupling with O-Phenylendiamine - Rahma Abdul Hameed Hasan; Ali Ibraheem Khaleel (Tikrit Journal of Pure Science)
This study includes the development of a new sensitive spectrophotometric method for the determination of a hydrochlorothaizide in aqueous solution and pharmaceultical preparations. The method is based on the oxidative coupling reaction of hydrochlorothaizide with O-phenylendiamine reagent in a acidic medium pH 1.5 in the presence of potassium ferricyanide  to produce an intense orange color, water soluble and stable product , which exhibits maximum absorption at 450 nm. Beer’s law is obeyed over the concentration arange 6 to 48 µg.ml-1 of hydrochlorothaizide, with a molar absorptivity of  3602.17  L.mo1-1 .cm -1 , Sandell’s sensitivity index of 0.03 µg.cm-2 , relative error range not more than 0.215% , and D.L 0.0835µg.ml-1 . The method has been successfully applied for the determination of hydrochlorothaizide in tablets.